2010
DOI: 10.1111/j.1442-200x.2010.03157.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CPS14217C>A genotype on valproic‐acid‐induced hyperammonemia

Abstract: These findings suggested that in epileptic patients undergoing VPA therapy, CPS14217A polymorphism and the number of coadministered anticonvulsants would be considered as risk factors for hyperammonemia, even if the serum VPA concentrations were controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…CPS1 4217C>A heterozygous and homozygous mutation carriers (CA and AA) had a greater risk of hyperammonaemia compared with wild‐type (CC) carriers. These results were consistent with those reported by previous studies . However, a recent study by Inoue et al .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…CPS1 4217C>A heterozygous and homozygous mutation carriers (CA and AA) had a greater risk of hyperammonaemia compared with wild‐type (CC) carriers. These results were consistent with those reported by previous studies . However, a recent study by Inoue et al .…”
Section: Discussionsupporting
confidence: 94%
“…This finding was consistent with that reported by Yagi et al . . However, recent research has indicated that γ‐GT rather than alanine aminotransferase levels were significantly higher in patients with hyperammonaemia .…”
Section: Discussionmentioning
confidence: 95%
“…Both heterozygous and homozygous carrier states of the T1405N polymorphism and concomitant administration of two or more anticonvulsants with VPA were shown previously to be independent risk factors for developing HA in the relatively small cohort of patients ( N = 79) from Japan and single case report from our laboratory [4, 5]. In the recent larger study, Yamamoto et al identified several other risk factors for HA in PWE, including VPA dose and use of hepatic enzyme inducers, although genetic polymorphism was not analyzed in this study [6].…”
Section: Discussionmentioning
confidence: 99%
“…The prior limited data from exclusively Japanese cohort suggested that patients treated with VPA and who carry the T1405N (4217C > A, rs1047891) missense single nucleotide polymorphism (SNP) in the carbamoyl phosphate synthetase 1 gene might be more likely to experience HA [4]. The main goal of this project was to investigate, for the first time in Caucasian cohort, if carbamoyl phosphate synthetase 1 (CPS1) gene T1405N missense variant can be associated with increased occurrence of HA in subjects treated with VP.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, CPS1 may be impacted by general mitochondrial dysfunction caused by toxic VPA metabolites. In a small study ( n = 79), the rs1047891A (4217C > A) polymorphism of CPS1 was associated with an increased risk of hyperammonemia when receiving combined treatment of VPA with two or more other antiepileptics [33]. This SNP is also associated with lower CPS1 activity [34].…”
Section: Introductionmentioning
confidence: 99%